R-SFCL and RRCOCS-TVC Based Cooperative Control for Enhancing LVRT Capability of DFIG System - Khan, Md Sabbir Haider; Mallik, Sanjeev Kumar (Trends in Sciences, 2022)
For the extraction of wind energy through a doubly-fed induction generator (DFIG), low voltage ride through (LVRT) is an essential technical requirement specified by the transmission system operator (TSO). Under a grid fault condition, DFIG should remain in connection with the grid for a certain minimum period and offer reactive power support as required by the TSO. A cooperative control scheme consisting of hardware solution through a superconducting resistance type fault current limiter (R-SFCL) and software solution constructed on the rotor reference current orientation control strategy (RRCOCS) with transient voltage control (TVC), is proposed in this paper to address the LVRT requirement. In the proposed control strategy, RRCOCS will limit the rotor current directly during a fault condition. The reactive power needs to be generated during fault to maintain grid code which is achieved through TVC. At the same time, improvement of stator terminal voltage, as well as suppression of stator current, is achieved by R-SFCL. The suppression of stator current by R-SFCL is also transformed to the rotor side aiding the rotor current limiting. The proposed cooperative scheme’s performance is simulated and tested on a 9 MW grid-connected DFIG wind system. The results obtained by the proposed strategy are compared with RRCOCS and RRCOCS-TVC. HIGHLIGHTS Independent software and hardware LVRT methods fail under severe faults and strict grid codes Software methods are challenged by current suppression and voltage support limits while the hardware methods involve high costs and undergo high thermal stress A cooperative LVRT can overcome the challenges and limitations associated with these independently deployed methods. The proposed R-SFCL device, in cooperation with RRCOCS-TVC, successfully meets the grid codes, and the transient behavior of the system's electrical and mechanical variables gets improved The proposed scheme helps reduce R-SFCL resistance, reduces its thermal stress, brings cost reduction in R-SFCL design, and improves its recovery characteristics. The listed improvement in R-SFCL can prevent the system from overcompensation and the adverse effects of recurring faults GRAPHICAL ABSTRACT